Reduksionisme lokalitas dalam Television ads (Sebuah Wacana Imperialisme Budaya) - Djati Prasetyani Hadi (Jurnal Paradigma, 2011)
Magnitude of the mass media, one of which lies in its ability to create a discourse about reality or rather a general truth. In critical studies, the ability of mass media in creating public discourse of reality or truth is in fact often exploited certain parties to make a new form of colonialism and relatively hidden. A media imperialism, which no longer associated with physical control but on “the mental framed” construction, where the strategy of imperialism carried out parallel with education instead of going to the spirit of liberation and equality in the box with the image of the Modern. This article attempts to unpack how the ad or TV ad in particular, as the product of the mass media which according to Chapman regarded as “one of Richest sources available for surveying the state of modern mythology” doing the process of media imperialism. Election issues “Locality” in TV ads were taken by two main considerations: first, that the issue is relatively crucial issues and enduring in the East and West relations or wealthy industrialist with the state Poor State or target industrialist. Second, while many parties attempt to show or demonstrate empathy towards the local community by providing motivation and facilities on facilities on the value-belief-behavior local to a go-publish, it coincided with efforts ethnicist it being popularized through the mediation of the mass media industry, participating as well industrial interests of the charged political economy and of course biased. Go-publish locality which was originally filled with the spirit of equality in the process it was defeated by the interests of industrialists created solely for the sake of the industrialists. In such a context, the localism in television viewing in general or in particular television ad is only present and mediate the ‘needs’ differentiation only and does not motivate concrete actions to realize the essence of equality which aspired at first. Image of ‘differentiation’ is what the media is packaged in a speech language (verbal &visual) that is also called as the process of formation of Mythology. This article attempts to unpack the process of media imperialism at the level of advertising creative production process, which often occurs even without the knowledge or awareness of the ‘author’ creativity of the ad itself.